2013
DOI: 10.1177/1352458513490542
|View full text |Cite
|
Sign up to set email alerts
|

Differential microRNA expression in blood in multiple sclerosis

Abstract: RRMS patients in remission had altered expression of miRNAs. We validated miR-145 as a potential diagnostic biomarker for the diagnosis of MS in blood, plasma and serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 29 publications
(38 reference statements)
1
77
0
3
Order By: Relevance
“…As such, these miRNAs may be differentially expressed in other immunemediated diseases and have broader implications on CD4 T cell development and differentiation. It is well established that miRNAs play key roles in the development and function of Tregs (Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013), and differential expression of miRNAs have been found in patients with multiple sclerosis (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…As such, these miRNAs may be differentially expressed in other immunemediated diseases and have broader implications on CD4 T cell development and differentiation. It is well established that miRNAs play key roles in the development and function of Tregs (Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013), and differential expression of miRNAs have been found in patients with multiple sclerosis (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs.…”
Section: Discussionmentioning
confidence: 63%
“…While genetic studies have identified genes critical to the immune system as being potential risk factors (Baranzini et al, 2009b;De Jager et al, 2009;Beecham et al, 2013), many of the genetic contributors to this disease are unknown. An emerging area of interest in multiple sclerosis has been genetic regulation at the microRNA (miRNA) level (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). MiRNAs are small, non-coding RNA that regulate gene expression and, thus, modify cellular pathways and disease processes (Ambros, 2004;Bartel, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of miRNA in MS has largely been used to identify a biomarker or understand peripheral immune responses in MS [8,19,9,20,21]. However, very few miRNA studies have been done to understand their role in the CNS in MS. A miRNA profiling study analyzing active and inactive MS lesions found that miRNAs may be regulating macrophage function in lesions, promoting the phagocytosis to clear myelin and debris [22].…”
Section: Discussionmentioning
confidence: 99%
“…L'utilisation de ces biopuces appliquée à différents tissus provenant de patients atteints de SEP a ainsi mis en évidence une altération de l'expression de nombreux miARN au cours de la maladie. La détection des miARN a été réalisée à partir de tissus (sang total [13,14], tissu nerveux [15,16], hippocampe [17]), de cellules (cellules mononucléées du sang [18][19][20], lymphocytes B [21][22][23] et T [11,20,[23][24][25][26], monocytes [27], microglie [27], cellules endothéliales [28,29]) ou de fluides extracellulaires (sérum/plasma [12,18,[30][31][32][33], LCR [34]). Nous répertorions de manière systématique dans cette revue, l'ensemble des données issues de la littérature concernant les miARN SYNTHÈSE REVUES miR-155 -/- [37]) sont résistantes à l'induction d'une EAE.…”
Section: Dérégulation Des Miarn Chez Les Patients Atteints De Sepunclassified
“…méthodes actuelles de diagnostic comme l'imagerie par résonnance magnétique (IRM) ou l'étude du LCR par ponction lombaire, leur détection (par qPCR) est rapide et peu coûteuse. Plusieurs études ont évalué l'utilisation des niveaux d'expression de miARN comme outil pour distinguer les patients atteints de SEP de sujets sains ou pour prédire les formes de SEP [18,32,34]. Les niveaux d'expression de certains miARN permettent en effet de diagnostiquer la SEP avec une précision de diagnostic supérieure à 70 % sur de petits échantillons.…”
Section: Th17unclassified